Graduates Perception on Job Search: A Critical Review - Maharjan, Sumi (Quest Journal of Management and Social Sciences, 2019)
Background:The impact of the increased popularity of the internet as a platform to search for jobs may benefit every job seeker as an alternative to generate employment opportunities. Graduates that emphasize on general skills have a higher likelihood of disparitywhile searching for jobs. Objectives:This paper explores graduates’ perceptionson the knowledge of how to search for jobs from relevant sourcesr. Methods:The theoretical review focuses on job search strategies, job choices and job accessibility through different sources, highlights the usefulness of job portals for job seekers to find the right job as per their skills and requirements. The existing literature has observed that many job search behaviors through different sourceshas been performed and these behaviors indicate that awareness level affects job seekers’ intentions to apply for jobs. Empirical studies indicate that thechoice of job search by graduates match between a worker’s education and job offered.General skills have a higher likelihood of mismatch at job searches in different countries. Findings:Still in many developing countries, due to lack of awareness of job portals, people are not getting the right jobs and alternatives of their current jobs by different sources. Conclusions:A comprehensive study on applicability of the internet job search is useful for employers, considering the introduction of new graduate recruitment programmers. It is also useful for those wishing to improve their existing ones as well as for institutions of higher education, to reconsider the type of knowledge and skills they provide in order to prepare their students for the real world of work. Implications: Graduates require proper awareness on job search sites and the concerned industry should focus on it as well.